Recurrence and functional outcomes of partial adrenalectomy: A systematic review and meta-analysis. (April 2015) - Nagaraja, Vinayak; Eslick, Guy D.; Edirimanne, Senarath
Abstract: Background: Partial adrenalectomy is typically performed for the treatment of hereditary and sporadic bilateral tumours, to reduce the risk of adrenal failure, particularly in younger patients. Partial adrenalectomy proposes a postoperative steroid-free course nevertheless, is associated with the risk of local recurrence. In this study we evaluate the recurrence and functional outcomes of partial adrenalectomy. Methods: A systematic search was conducted using MEDLINE, PubMed, EMBASE, Current Contents Connect, Cochrane library, Google Scholar, Science Direct, and Web of Science. The search identified 60 relevant articles reporting on patients who underwent partial adrenalectomy. Data was extracted from each study and used to calculate a pooled event rate and 95% confidence interval (95% CI). Results: The overall recurrence rate was 8% (95% CI: 0.05–0.12) and the 85% (95% CI: 0.78–0.9) of the patients were steroid free. The recurrence rates were the least in the retroperitoneoscopic group 1% (95% CI: 0–0.04) and Conn's syndrome group 2% (95% CI: 0.01–0.05) and highest in open group 15% (95% CI: 0.07–0.28) and Pheochromocytoma group 10% (95% CI: 0.07–0.16). Steroid independence rates were best in the Conn's syndrome group 97% (95% CI: 0.85–0.99) and laparoscopic group 88% (95% CI: 0.75–0.95). Conclusions: Partial adrenalectomy can obviate the need for steroid replacement in the majority of patients and local recurrence rates appear to be infrequent. For patients with hereditary and bilateral adrenal tumours, partial adrenalectomy should be recommended as a primary surgical approach whenever possible. Highlights: Parathyroidectomy for PHPT potentially improves function and quality of life. Currently, there is no quantitative evidence to support this for all studies. This study provides evidence that parathyroidectomy improves the quality of life.